Siple Dome Methane Record - Brook, Edward J. (IEDA: US Antarctic Program Data Center, 2003)
This data set is part of the WAISCORES project, an NSF-funded project to understand the influence of the West Antarctic ice sheet on climate and sea level change. WAISCORES researchers acquired and analyzed ice cores from the Siple Dome, in the Siple Coast region, West Antarctica. Brooks measured methane in approximately 196 samples between 55.6 and 738.5 m (0-20 ka) in the Siple Dome ice core, and then extended the Siple Dome methane record at medium resolution down to about 860m, corresponding to an age of about 45 ka. The team compared the results with data from the Greenland Ice Sheet Project 2 (GISP2) and the Greenland Ice Core Project (GRIP).